Exploring Science Teachers’ Translation of Nature of Science (NOS) Knowledge to Pedagogical Content Knowledge (NOS PCK) - Jain, Jasmine; Mok, Shu Jin; Lee, Yee Ling (UUM Press, 2025)
Purpose - This study is part of a comprehensive investigation conducted in Malaysia, examining science teachers' understanding of the Nature of Science (NOS) and their ability to translate this knowledge into Pedagogical Content Knowledge (PCK) for NOS. This paper specifically examines how teachers apply their NOS knowledge to develop NOS PCK in classroom settings. Methodology - A qualitative approach was employed, involving observations of both practical and non practical lessons, as well as semi-structured interviews with five in-service science teachers from a school in Petaling Perdana, Selangor. The teachers were chosen based on their experience in teaching science and their understanding of NOS. Lesson observations were guided by a structured checklist, while thematic analysis was used to interpret interview data, providing insights into the rationale behind their teaching methods related to NOS PCK. Findings - The study found that Malaysian in-service science teachers face significant challenges in translating their understanding of NOS into effective teaching practices. There is a noticeable gap between teachers' conceptual knowledge of NOS and their PCK implementation. Teachers frequently missed opportunities to integrate key NOS concepts into their lessons and often portrayed scientific methods as fixed procedures while presenting science as static knowledge. These practices reflect a limited understanding of NOS principles. Significance - The findings underscore the urgent need for ongoing professional development to improve teachers' NOS knowledge and their ability to integrate it into their teaching. The science curriculum should include clear guidelines to support the incorporation of NOS concepts, ultimately fostering improved scientific literacy among students